Improving Assessment of Foreign Language Proficiency in Internationally Majoring Students - N. L. Kobiakova (Vestnik MGIMO-Universiteta)
The author considers the issues related to the development of the theoretical platform and the methodology for a model used to control and evaluate educational achievements at the Russian-based university-level foreign-language using such foreign practices as merit point system, testing technology and traditional controls. Having analyzed European practices of control and evaluation of students' foreign language proficiency, in particular, the experience of France, she advocates for the adoption by the national university system of the best available foreign methodology in the field. The article depicts the proprietary model for the comprehensive assessment of the educational outcomes of the internationally majoring students in the French language. The model, customized for Russian universities, is based on the professionally oriented competence-based practical course of the French language for internationally majoring students designed by the author. With the regard to that content and basing on DELF, DALF and TCF language tests and exercise systems for the French language studies by European and Russian practitioners, she advances her own testing, communication and translation exercises toolbox. That comprehensive evaluation model was successful tested at the MGIMO. In the course of that experiment, national testing techniques and the content of linguistic tests and didactic tools were streamlined with the European requirements.